Ways of Representing Geographical Space in the Journal “Children’s Reading for the Heart and Mind” (1785–1789) - Tatyana A. Alpatova (Два века русской классики)
The article examines the ways of presenting the geographic theme in the journal “Children’s Reading for the Heart and Mind,” identifies their typology, taking into account the problem-thematic and genre-poetic features of the publications. The study relies on the publications of the journal from 1785 to 1789, thematically related to the problems of geography and containing geographic images, both detailed and local. The article shows that the problem-thematic composition and content of the publications were largely based on geographic imagery. This corresponded to the main educational guidelines of the era, i. e., a combination of entertaining and useful reading. The article distinguishes four main types of representation of geographic imagery: allegorical, didactic- pedagogical, educational, and subjective-emotional. The ideological pragmatics of appeals to geographic imagery in the journal rises from several stable ideologemes of the Enlightenment: the natural equality of people, the openness and diversity of the world, the expansion of man in it. The dualism of the journal’s concept allowed the publishers to combine educational and Rousseauist approaches in interpreting the picture of the universe.